Solar-Powered Irrigation and Farm Performance: An Impact Evaluation from Kashmir Valley, India - Ahmad Peer, Quadri Javeed; Rashid, Irfath; Tabina; Kubrevi, Syed Shafat; Shah, Immad A.; Para, Irshad Ahmad (Indian Journal of Extension Education, 2026)
The growing demand for energy and the rising costs of traditional irrigation methods have increased the need for sustainable options in agriculture. Solar water pumps are a practical and eco-friendly choice, especially in regions with high solar exposure like Jammu and Kashmir. According to data collected from JAKEDA (2024), a total of 1,309 beneficiaries have used solar water pumps under the PM-KUSUM scheme. The study conducted during 2025, evaluated how adopting solar water pumps affects important agricultural aspects, such as irrigation costs, crop production, crop quality, diversification, and plant growth in three selected districts, namely; Anantnag, Pulwama, and Baramulla (with a large number of functioning solar water pumps). By applying the results of the Wilcoxon signed-rank test to data collected from growers, significant differences between the conditions before and after adoption were recorded. A significant decrease in labor and diesel expenses, along with notable gains in both crop yield and quality, was found. Diversified crops with high market value have improved, and overall plant growth has seen considerable progress since adopting solar water pumps.